Comparison of Practices: Guarantee Perfection Mechanisms for Public Assets in Indonesia, Singapore, and Austria - Kuras Purba (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
The use of public assets as collateral in modern financingcreates an urgent need for a perfection mechanism that canguarantee legal certainty for creditors, the state, and third parties. In thecontext of financial market globalisation, countries are required to ensure that everysecurity interest granted on public assets has a transparent status, isverifiable, and is able to enforce the principle of priority. A comparative study betweenIndonesia, Singapore, and Austria shows substantial differencesin the registration regime, public notification mechanism, priority position,and constitutional restrictions related to the use of public assets as collateral.This article analyses the perfection mechanisms applicable ineach jurisdiction, covering the stages of registration, publicnotice, possession, and control mechanisms.The analysis shows that Indonesia still faces serious problemsin the form of legal fragmentation, the absence of a centralised registry, andunclear restrictions on the non-alienation of public assets. Meanwhile, Singaporehas developed an integrated system based on notice filing through ACRA, whichis oriented towards efficiency and transparency, while Austriaemphasises creditor protection through the Registerpfandrecht system, whichcombines the requirements of authentic deeds and formal public registration.This study recommends the establishment of a centralised security registration agency, reform of constitutional restrictions on public assets, andharmonisation of national perfection mechanisms with international practicesto support strategic government financing.